European Cross-Border Cooperation - Balak, Ilona O. (Lesya Ukrainka Volyn National University, 2023)
The publication outlines the thematic structure of the lecture materials, presents questions for seminar classes and test tasks for self-assessment, and a list of recommended references. It is recommended for students of 4th year for the bachelor’s degree preparation, specialty 291 «International Relations, Public Communication and Regional Studies», educational and professional program «International Relations»
Keywords: Theoretical basis of cross-border cooperation; Euroregions in Western Europe; Development of euroregions in Central Eastern Europe; 327.7(4)